Birth control methods used by selected urban poor couples - Ranches, Alice Dacocos; Malicdem, Eleanor A. (2005.)
This study looked into the birth control methods used by couples in Covenant Village, Barangay Bagong Silangan, District II, a depressed urban community in Quezon City. Convenience sampling was implemented using a survey questionnaire composed of two parts: Part I has solicited information about age, number of children, type of work, income; and Part II has solicited information about (a) the source of information in using birth control methods, (b) the period when couples decided to use birth control methods, (c) reasons for using birth control method, (d) the decision maker in using birth control methods, (e) the user of the specific type of birth control method and (f) the specific type of birth control method used by couples. Survey questionnaires were distributed to thirty (30) housewives. Twenty-three (23) of them were using birth control methods. The data was analyzed using descriptive methods such as frequency ranks and central tendencies (mean analysis). This study showed that knowledge about birth control methods came from health centers, church parenthood programs, hospitals, door-to-door information dissemination, sex education lectures and acquaintances. It was also found that the reason for using birth control methods were the following: (1) desire to limit the number of children, (2) poverty; and (3) birth spacing among the children. The urban poor couples in the study preferred to use birth control methods after their second child. Majority of the couples said that the decision to use birth control methods was consensus, while in cases where only one decides, the husband is the principal decision maker. Most of the couples practice natural birth control methods and what they usually use is rhythm or calendar method. Also, this study found that both the husband and wife use different methods of artificial birth control.
Thesis (BSHE)--University of the Philippines Diliman.
Keywords: Birth control -- Philippines -- Quezon City